Personality, thought, and political behavior of the local political ulama figure in Pandhalungan Indonesia - Arifin, Samsul; Baharun, Mokhammad (Penerbit Universiti Kebangsaan Malaysia, 2022)
Political behavior is also determined by the interaction and struggle of the politician’s personality. This paper examines the personality, thoughts, and political behavior with the vision of the late KHR. Ach. Fawaid As’ad, one of the local political figures Pandhalungan from Islamic Boarding School Salafiyah Syafi’iyah Sukorejo Situbondo. The study used a qualitative approach of ethnographic-hermeneutic type. Data comes from documents and field notes. Result: Personality Kiai Fawaid, which has the character of patience and sincerity (dimension of neurotism); socializing, energetic, and dominant (extraversion dimensions); artistic, open to new ideas, and uphold the values of Islamic Boarding School (dimension of openness to experience), forgiving and altruism (dimension of agreeableness); discipline; organizational, and obedient rules (conscientiousness dimension). Kiai Fawaid had thoughts that became political decisions-political parties or candidates in the election because of political considerations as a means of NU’s struggle and for the benefit of the ummah. As for its implementation, it goes to political parties to improve the system and organize the nation starting from the district level. Kiai Fawaid’s political thoughts and behavior is related to the character of his personality, especially the dimensions of openness to experience and agreeableness. This research is used as material for the development of political science and fiqh siyasah.